2000
DOI: 10.1161/01.atv.20.6.1572
|View full text |Cite
|
Sign up to set email alerts
|

LDL Receptor–Related Protein Mediates Uptake of Aggregated LDL in Human Vascular Smooth Muscle Cells

Abstract: Abstract-Foam cell formation is a key event in the onset and progression of atherosclerotic lesions. We have previously reported that internalization of aggregated low density lipoproteins (agLDLs) by vascular smooth muscle cells (VSMCs) produces cholesteryl ester (CE) accumulation in these cells. The aim of this study was to analyze whether the low density lipoprotein receptor-related protein (LRP) mediates the uptake of agLDL by VSMCs. First, immunocytochemistry and fluorescence microscopic analysis with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 136 publications
(169 citation statements)
references
References 58 publications
9
158
1
1
Order By: Relevance
“…AgLDL was prepared as described previously. 17,18 Levels of thiobarbituric acid-reactive substances (Ͻ1.2 mmol of malonaldehyde per milligram of protein LDL) remained similar to those in nLDL after LDL aggregation.…”
Section: Ldl Preparationmentioning
confidence: 83%
See 3 more Smart Citations
“…AgLDL was prepared as described previously. 17,18 Levels of thiobarbituric acid-reactive substances (Ͻ1.2 mmol of malonaldehyde per milligram of protein LDL) remained similar to those in nLDL after LDL aggregation.…”
Section: Ldl Preparationmentioning
confidence: 83%
“…17,18 Non-LRP-expressing VSMCs were obtained by treatment of the cells with antisense LRP oligodeoxynucleotides (ODNs; 10 mol/L) as described previously. [17][18][19] …”
Section: Vsmc Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages attempt to clear the particles and become filled with esterified cholesterol droplets. We and others have demonstrated that LRPs play a crucial role in the uptake of agLDL either in vascular smooth muscle cells or in macrophages 33, 73. Moreover, our group has reported a higher efficacy of LRP5 than LRP1 for promoting CE accumulation in human macrophages 22 which was related to an early saturation of LRP1 lipid uptake activity.…”
Section: Discussionmentioning
confidence: 67%